Improving continence management for people with dementia in the community in Aotearoa, New Zealand: Protocol for a mixed methods study - Vanessa Burholt (PLOS ONE, 2023)
Background: The number of people living with dementia (PLWD) in Aotearoa New Zealand (NZ) was estimated at 96,713 in 2020 and it is anticipated that this number will increase to 167,483 by 2050, including an estimated 12,039 Māori (indigenous people of NZ) with dementia. Experiencing urinary incontinence (UI) or faecal incontinence (FI) is common for PLWD, particularly at the later stages of the disease. However, there is no robust estimate for either prevalence or incidence of UI or FI for PLWD in NZ. Although caregivers rate independent toilet use as the most important activity of daily living to be preserved, continence care for PLWD in the community is currently not systematised and there is no structured care pathway. The evidence to guide continence practice is limited, and more needs to be known about caregiving and promoting continence and managing incontinence for PLWD in the community. This project will seek to understand the extent of the challenge and current practices of health professionals, PLWD, caregivers and family; identify promising strategies; co-develop culturally appropriate guidelines and support materials to improve outcomes; and identify appropriate quality indicators so that good continence care can be measured in future interventions. Methods and analysis: A four-phase mixed methods study will be delivered over three years: three phases will run concurrently, followed by a fourth transformative sequential phase. Phase 1 will identify the prevalence and incidence of incontinence for PLWD in the community using a cohort study from standardised home care interRAI assessments. Phase 2 will explore continence management for PLWD in the community through a review of clinical policies and guidance from publicly funded continence services, and qualitative focus group interviews with health professionals. Phase 3 will explore experiences, strategies, impact and consequences of promoting continence and managing incontinence for PLWD in the community through secondary data analysis of an existing carers’ study, and collecting new cross-sectional and longitudinal qualitative data from Māori and non-Māori PLWD and their caregivers. In Phase 4, two adapted 3-stage Delphi processes will be used to co-produce clinical guidelines and a core outcome set, while a series of workshops will be used to co-produce caregiver resources.